2010
DOI: 10.1080/10916461003681695
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Temperature and Impeller Speed on Mechanically Induced Gas Flotation (IGF) Performance in Separation of Oil from Oilfield-Produced Water

Abstract: The effect of temperature and impeller speed on the performance of induced gas flotation (IGF) systems for the removal of oil from produced water in different ranges (5-300 g/L) of total dissolved solids (TDS) was investigated in a pilot plant study. Furthermore, it was evaluated whether the IGF pilot plant effluent could reach the 15 mg/L outlet oil content as required by Article VI of the Kuwait Convention for Persian Gulf region, before being discharged to the sea. The results showed that oil removal effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…Both methods are capable of reducing the oil concentration in the treated produced water to 15 ppm which is typical of the environmental discharge limits in many parts of the world [8] Filtration systems…”
Section: Gas Floatation Systemsmentioning
confidence: 99%
“…Both methods are capable of reducing the oil concentration in the treated produced water to 15 ppm which is typical of the environmental discharge limits in many parts of the world [8] Filtration systems…”
Section: Gas Floatation Systemsmentioning
confidence: 99%
“…A few studies on the effect of temperature on flotation have also been carried out. Strickland investigated the temperature effect on oil recovery using gas flotation, obtaining higher efficiencies when working at 60 °C than at ambient conditions. Mastouri et al investigated the effect of temperature on the performance of IGF systems for the removal of oil from PW in different ranges of total dissolved solids (TDS). They obtained increased oil removal efficiencies when the temperature was raised from 20 to 80 °C at high TDS.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies on the effect of temperature on flotation have also been carried out. Strickland investigated the temperature effect on oil recovery using gas flotation, obtaining higher efficiencies when working at 60 °C than at ambient conditions. Mastouri et al investigated the effect of temperature on the performance of IGF systems for the removal of oil from PW in different ranges of total dissolved solids (TDS).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, various conditions, such as impeller and stator size, design, impeller rotation speed, flow rate, and vessel capacity were considered and analyzed. Previous research analyzed the IGF performance according to the rotational speed of impeller and fluid temperature using total dissolved solids (Mastouri et al, 2010). They found that temperature changes had a more direct effect on the removal efficiency than on the impeller rotation speed.…”
Section: Introductionmentioning
confidence: 99%